EPISTEMOLOGY: ARGUMENTS AGAINST PHENOMENALISM - Z. Fikri (Khazanah: Jurnal Studi Islam dan Humaniora, 2019)
In this essay 1 examine one model of critical episternologies, namely the phenomenalism. It ts a form of anti-realism; the phenomenalist denies the existence of a physical world when it is unperceived. I argue that the phenomenalist does not provide us with a meaningful and useful advancement in our understanding of experience and the world surroundings us. Against them i say that the appearances of physical objects are dependent on the nature of the object it-self, the condinons of perceiver and the light falls into the object, The notion of standard conditions put forward by the phenomenalist lead them into favouritism and committed to representationalism